Occupation Choice in the Rural Labor Market from the Córdoba Department in Colombia - Anaya Narváez, Alfredo R.; Pinedo López, Jhon W.; Doria Sierra, Carlos F. (Economia agro-alimentare/Food Economy - Open Access, 2023)
This article aims to establish if the rural labor market of the Department of Córdoba holds structural problems that encourage members of the rural labor force to search for other work alternatives in the urban area, by identifying factors related to supply conditions, such as human capital, age, home location area [dominion], gender, and others that affect the choice of the kind of work. A multinomial Logit econometric model was estimated to achieve this purpose, using statistical information from the Great Integrated Household Survey (GIHS) carried out by DANE from the third quarter of 2019, whereby the employment choice of men and women in rural and urban areas was analyzed among four categories, i.e. low manual (1), high manual (2), low non-manual (3), and high non-manual (4). Results reveal that the estimated model shows a good fit and that the education, gender, and domain variables are statistically significant with confidence levels greater than 95%. Similarly, figures of the marginal effects, which reveal changes in probabilities of choosing one job or another, may be evidence of the little consolidation that the rural labor market has to motivate its inhabitants to choose countryside activities, allowing to conclude that the migration phenomenon from the countryside to the city is largely explained by the search for better jobs, thus revealing the structural problems of the rural labor market in the Cordoba Department.